2007
DOI: 10.1126/science.1139601
|View full text |Cite
|
Sign up to set email alerts
|

Model Projections of an Imminent Transition to a More Arid Climate in Southwestern North America

Abstract: How anthropogenic climate change will affect hydroclimate in the arid regions of southwestern North America has implications for the allocation of water resources and the course of regional development. Here we show that there is a broad consensus among climate models that this region will dry in the 21st century and that the transition to a more arid climate should already be under way. If these models are correct, the levels of aridity of the recent multiyear drought or the Dust Bowl and the 1950s droughts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
1,431
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,894 publications
(1,494 citation statements)
references
References 18 publications
57
1,431
2
4
Order By: Relevance
“…In addition, the dust season, defined by the length between the first and last events detected at these sites, has become longer (see section S2 for details), consistent with an earlier onset of dust events reported by Hand et al [2016]. Climate models have robustly predicted an incipient spring drying trend in this region [ Seager et al ., 2007; Cook et al ., 2015; Dai , 2013; Gao et al ., 2014], and the observed dust trend could thus be an early signal of its development.…”
Section: Intensification Of Dust Storm Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the dust season, defined by the length between the first and last events detected at these sites, has become longer (see section S2 for details), consistent with an earlier onset of dust events reported by Hand et al [2016]. Climate models have robustly predicted an incipient spring drying trend in this region [ Seager et al ., 2007; Cook et al ., 2015; Dai , 2013; Gao et al ., 2014], and the observed dust trend could thus be an early signal of its development.…”
Section: Intensification Of Dust Storm Activitymentioning
confidence: 99%
“…Climate model projections suggest a consistent trend toward an increasingly arid climate in the subtropics, including the southwestern United States [ Schubert et al ., 2004; Seager et al ., 2007; Cook et al ., 2015; Prein et al ., 2016]. The predicted drying trend over arid and semiarid regions aids speculation of more frequent dust storms and even another “Dust Bowl” in the coming decades.…”
Section: Introductionmentioning
confidence: 99%
“…Denton et al, 2010). Furthermore, the comparison between AOGCM simulations of the LGM and the paleoclimate data demonstrated that hydrologic quantities such as evapotranspiration, soil moisture and runoff will require additional paleoclimate proxy data to reduce the model uncertainty (Seager et al, 2007;Waliser et al, 2007) The 238 U concentration of the spiked CRM145 was 15.7451 ng/g. The concentration of 236 U was calculated using an error weighted average and was found to be 0.91987 ± 0.00063 ng/g (2σ, MSWD = 0.60, n = 18).…”
Section: Resultsmentioning
confidence: 99%
“…Projecting into the 21 st century, increased anthropogenic greenhouse emissions, primarily CO 2 from fossil fuel combustion, will cause changes in the seasonal and long-term availability of water, shifting the balance between precipitation and evapotranspiration (Seager et al, 2007). Changes in the spatial patterns and amount of rainfall caused by this hydrologic intensification in the climate system will also affect water resources (Meehl et al, 1999;Huntington, 2006), annual snow packs (Mote et al, 2004;Barnett et al, 2005), species migration (Walther et al, 2002), and may result in more extreme weather events such as flooding and drought (Meehl et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation